Recovery of phenolic antioxidants from Syrah grape pomace through the optimization of an enzymatic extraction process - Meini, María Rocío (2019)
Phenolic compounds are highly valuable products that remain trapped in grape pomace, an abundant winery by-product. Therefore, efficient extraction procedures of these compounds represent a route for grape pomace valorisation. Here we performed a screening of the factors affecting the aqueous enzymatic extraction of phenolic compounds from Syrah grape pomace, including the following independent variables: temperature, pH, pectinase, cellulase and tannase; and a subsequent optimization through response surface methodology. At the optimal region, the enzymatic treatment enhanced the extraction yield of phenolics by up to 66% and its antioxidant capacity by up to 80%, reducing the incubation time and enzyme doses in respect to previous studies. We found that tannase raises the antioxidant capacity of the extract by the liberation of gallic acid, while cellulose favours the liberation of p-coumaric acid and malvidin-3-O-glucoside. We also tested the procedure in different grape pomace varieties, verifying its wide applicability.